2020
DOI: 10.1021/acs.jmedchem.9b01936
|View full text |Cite
|
Sign up to set email alerts
|

Triazolo-Peptidomimetics: Novel Radiolabeled Minigastrin Analogs for Improved Tumor Targeting

Abstract: MG11 is a truncated analog of minigastrin, a peptide with high affinity and specificity toward the cholecystokinin-2 receptor (CCK2R), which is overexpressed by different tumors. Thus, radiolabeled MG11 derivatives have great potential for use in cancer diagnosis and therapy. A drawback of MG11 is its fast degradation by proteases, leading to moderate tumor uptake in vivo. We introduced 1,4-disubstituted 1,2,3-triazoles as metabolically stable bioisosteres to replace labile amide bonds of the peptide. The "tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(78 citation statements)
references
References 58 publications
6
72
0
Order By: Relevance
“…It has been shown that the amide-to-triazole switch leads to peptidomimetics with maintained lipophilicity. In the studied cases, single or multiple substitutions of (up to three) amide bonds with triazoles did not change the logD 7.4 values of peptides consisting of at least six amino acids [ 77 , 82 , 93 , 112 ]. Even though 1,4-disubstituted 1,2,3-triazoles are good bioisosteres of trans -amide bonds by mimicking electronic and steric features, a few essential differences exist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the amide-to-triazole switch leads to peptidomimetics with maintained lipophilicity. In the studied cases, single or multiple substitutions of (up to three) amide bonds with triazoles did not change the logD 7.4 values of peptides consisting of at least six amino acids [ 77 , 82 , 93 , 112 ]. Even though 1,4-disubstituted 1,2,3-triazoles are good bioisosteres of trans -amide bonds by mimicking electronic and steric features, a few essential differences exist.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the Corey-Fuchs reaction for the transformation of aldehydes to alkynes can be employed for the synthesis of Boc-protected α-amino alkynes [ 81 ]. However, it is known that this approach may lead to partial racemisation of the α-amino alkyne [ 52 , 56 , 82 ]. The use of α-amino alkynes as a mixture of enantiomers results in the formation of diastereomers when used for peptide synthesis and additional measures (i.e., purification of the alkynes using chiral HPLC or separation of the resulting diastereomeric peptide products by HPLC) have to be taken into account.…”
Section: Synthesis Of Triazolo-peptidomimeticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability was not considerably further improved by additional triazole insertion at Ala-Tyr or Tyr-Gly. On the other hand, the insertion of triazoles at Tyr-Gly, Ala-Tyr, DGlu-Ala had a remarkable effect on tumor uptake, which was however clearly inferior to DOTA-MGS5 [ 28 , 30 , 44 ]. The introduction of an N -methylated peptide bond at Nle-Trp showed both effects of increased stability and improved receptor interaction.…”
Section: Discussionmentioning
confidence: 99%
“…With the aim of further improving the in vivo stability of DOTA-MGS5, we have explored additional modification of the peptide sequence. The amino acid proline (Pro) is a promising candidate for amino acid exchange and forms a tertiary amide bond which similarly to N -methylated peptide bonds and triazoles may improve the stability in vivo [ 27 , 30 ]. In this study, a preliminary preclinical characterization of the new MG analog DOTA-DGlu-Pro-Tyr-Gly-Trp-( N -Me)Nle-Asp-1Nal-NH 2 ( 1 ) was carried out focusing on the enzymatic stability of the 177 Lu-labeled radiopeptide in vivo.…”
Section: Introductionmentioning
confidence: 99%